Remnants of European settlements in the Hooghly district of West Bengal - Roy, Keka Dutta (2014)
Through centuries, the area occupied by the Hooghly district of West Bengal has seen the rise and fall of the colonial ambitions of the Portugese, the Dutch, the French, the Danish and the British. Towards end of the 16th century, they successively founded factories(trading settlements) along the western banks of the river Hooghly being a strategic region.Thus grew several river ports each presided over by a different settlement. Each of the ports would rise to prominence only to be overshadowed by the next till the British ousted all the competitors. Today, traces of various European settlements remain etched in the port towns of the Hooghly district namely, Serampore, Chandannagar, Chinsurah, Hooghly and Bandel and the remnants of these past interactions are distinguishable making a brightly coloured mosaic of cultures.The Europeans built grand structures, peppered to local language and food with their own idioms.Notable among the colonial heritage sites are the Danish Governor’s House, St Olaf’s Church, Serampore college, the Baptist Mission and the English cemetery at Serampore.Chandannagore still upholds the French, Governor Dupleix’s residential palace, the Sacred Heart Church, the dilapidated gateway entrance and the grand promenade called ‘Quai Dupleix’.At Chinsurah, one sees the Armenian church of St. John the Baptiste, Dutch Commissioners House, the Dutch cemetery and the Clock Tower of the British times.Hooghly witnesses the Portuguese church at Bandel.This article aims at building awareness and consciousness for the task of preservation, conservation and maintenance of the colonial heritage the region, well seen in photographs, painting, annotation in books and journals which are often in danger of being wiped out with the economic changes in the district landscapes, with the rapid altering political, social, cultural circumstances and the changing architectural requirements of the times.